The effects of protected areas on the ecological niches of birds and mammals - Santangeli, Andrea; Mammola, Stefano; Lehikoinen, Aleksi; Rajasärkkä, Ari; Lindén, Andreas; Saastamoinen, Marjo (Nature Publishing Group, 2022)
Protected areas are a cornerstone for biodiversity conservation, and typically support more natural and undisturbed habitats compared to unprotected lands. The effect of protected areas on intra-specific ecological niche has been rarely investigated. Here, we explore potential differences in ecological niche properties of birds and mammals across protected and unprotected areas, and relate such differences to species traits. We combine two decades of survey data of birds and mammals from protected and unprotected areas, and apply robust matching to obtain a set of environmentally comparable protected and unprotected sites. Next, we calculate intra-specific niche volume change and habitat shift between protected and unprotected areas, and use generalized linear mixed models to explain these responses with species traits (habitat specialization, body mass, diet, and red list status). The majority of bird and mammal species (83% and 90%, respectively) show different habitat use when occurring within and outside protected areas, with the magnitude of this shift highly varying across species. A minority of species (16% of birds and 10% of mammals) do not change their niche volume nor shift their habitat between protected and unprotected areas. Variation in niche properties is largely unrelated to species traits. Overall, the varying ecological niche responses of birds and mammals to protected areas underscore that there is no universal niche-based response, and that niche responses to land protection are species-specific.
Keywords: biodiversity; conservation; protected areas; ecological niches; birds; mammals